Epidemiology of oral, salivary gland and pharyngeal cancer in children and adolescents between 1970 and 2011. (April 2017) - Levi, Shai; Zini, Avraham; Fischman, Stuart; Czerninski, Rakefet
Highlights: Knowledge is lacking about epidemiology of oral salivary gland and pharyngeal cancer in the young. This study analyzes the disease's demographic and clinical data of 42 years period. The relationship between the variables in this age group becomes apparent. Frequencies of tumor types and sites are different between 0–13 and 14–19 years of age. Diagnosis of nasopharyngeal cases was significantly higher among males than females. Abstract: Objectives: The age of oral and pharyngeal cancer patients has reportedly decreased over the last decade, but most of the peer-reviewed literature regarding oral and pharyngeal cancer in individuals 0–19 years of age (Y) is limited to specific tumor sites and/or types, or a small number of cases. Our aim is to characterize oral, salivary gland and pharyngeal cancer (OSPC) in 0–19 Y in order to improve knowledge of the disease in young individuals. Methods: Data on OSPC between 1970 and 2011 was taken from the Israel National Cancer Registry, and included patient age, gender, tumor site and tumor type. Data analysis was performed by using IBM SPSS, Winpepi software and Joinpoint Regression Program. alpha < 0.05 was deemed statistically significant. Results: A total of 13, 863 OSPC cases were diagnosed with 2.6% (N = 357) of 0–19 Y. The male to female ratio was 1.5:1. The rates of diagnosis decreased between 1991 and 2011 and were not significantly different between the genders. The nasopharynx was the leading tumor site (42.3%) followed by the salivary glands (20.5%), and both were more common in 14–19 Y. The tonsils and other pharyngeal sites were common among 0–13 Y. The main tumor types were lymphomas (20.7%) and carcinomas (19.9%). Conclusions: The general characteristics of OSPC remained unchanged over the last four decades. This may imply that environmental factors have not had any effect. Males are affected more than females and might have a genetic predisposition for nasopharyngeal malignancy. Health care providers should be aware of the common sites and tumor types among children and adolescents.